2017
DOI: 10.1007/s12602-017-9314-6
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Selection and Identification of Potential Probiotics Isolated from the Gastrointestinal Tract of Nile Tilapia, Oreochromis niloticus

Abstract: Fish gut bacteria can be used as probiotics for aquaculture. The aim of this study is to screen and identify beneficial probiotic bacteria from the gut of Nile tilapia, Oreochromis niloticus. Nine out of one hundred thirty-five isolates were non-pathogenic through intraperitoneal injection and had antibacterial activities with at least a strain from the five isolated fish pathogens, Aeromonas sobria, Aeromonas hydrophila, Pseudomonas aeruginosa, Pseudomonas putida, and Staphylococcus aureus. Further tests show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 57 publications
3
33
1
7
Order By: Relevance
“…Furthermore, it was also reported that Lysinibacillus species could be used as probiotics in fish (Reda et al . ). However, there is no detailed information available about L. xylanilyticus species in the literature.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, it was also reported that Lysinibacillus species could be used as probiotics in fish (Reda et al . ). However, there is no detailed information available about L. xylanilyticus species in the literature.…”
Section: Discussionmentioning
confidence: 97%
“…It was suggested that bacteriocin purified from Lysinibacillus JX416856 isolate could present an alternative therapeutic agent in the control of food pathogens (Ahmad et al 2014). Furthermore, it was also reported that Lysinibacillus species could be used as probiotics in fish (Reda et al 2017). However, there is no detailed information available about L. xylanilyticus species in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…agalactiae . It was maintained in TSB medium reported in the successful development of a competitive exclusion culture from different animals including fish culture [36,37]. This medium is relatively inexpensive, easily obtainable and easily reproducible from off-the-shelf-ingredients, also appropriate to support the growth of aerobic and anaerobic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…An opaque halo around the cultured bacteria due to crystals of the calcium salt of the fatty acids liberated by lipolysis was regarded as a positive lipase activity. The presence of amylolytic activity was determined by starch medium consisting of 12 g starch, 4 g peptone, and 12 g agar per liter [82]. The plates were then covered with a 1% Lugol's iodine solution for the detection of a clear halo in a dark field, representing a positive activity.…”
Section: Enzyme Production and Spore Formationmentioning
confidence: 99%